A COMPARATIVE ANALYSIS OF MALE AND FEMALE CUSTOMERS PERCEPTION OF BRILINK POS TERMINAL PERFORMANCE IN MANADO - Wungow, Abigail; Worang, Frederik G.; Saerang, Regina T. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: The use of Point-of-Sales Terminals or also known as EDC Machine overcome problems that can come up when customers make a transaction. Some of the problems in question are security when carrying cash, consumer awareness about the existing non-cash system, perceived ease of transaction and of course the benefits that can be felt when transaction non-cash using POS Terminal EDC machine. This study aims to analyze whether there are significant differences between male and female customers perception on BRILink POS Terminal performance based on Security of Operation, Consumer Awareness, Perceived Ease of Use, and Perceived Usefulness. This research uses quantitative method with comparative analysis. Questionnaire in this case is used to collected data from respondents. This research tests through compare means, independent sample T-test in a sample of 100 respondents, divided 50 male and 50 female customers in Manado. Findings of this research indicate that there is no significant difference perception of male and female customers perception on BRILink POS Terminal performance. From the results, it is recommended for BRI Company continue to improve the service quality, especially in terms of consumer awareness about transactions at BRILink using POS Terminal. Keywords: point-of-sales, security of operation, consumer awareness, peou, pu, BRILink